2008
DOI: 10.1021/cr078198u
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, Biology, and Medicinal Potential of Narciclasine and its Congeners

Abstract: Ornamental flower growers know that placing a cut daffodil (a.k.a. narcissus) in a vase with other flowers has a negative effect on the quality of those flowers and significantly shortens their vase life. Furthermore, a common horticultural practice for the cultivation of narcissus flowers involves the introduction of cuts on the bulbs before immersing them into water. The mucilage that leaches out from the cuts is constantly removed by frequent changing of water and this leads to sprouting. These observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
375
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(397 citation statements)
references
References 201 publications
(589 reference statements)
12
375
0
10
Order By: Relevance
“…Many of these plants have been used historically for the treatment of cancer, since the oil of the daffodil Narcissus poeticus L. was used by Hippocrates of Kos [5]. The application of narcissus oil in cancer management continued during the middle ages in China, North Africa and Central America [6]. The major components isolated from the Amaryllidaceae plant family are alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these plants have been used historically for the treatment of cancer, since the oil of the daffodil Narcissus poeticus L. was used by Hippocrates of Kos [5]. The application of narcissus oil in cancer management continued during the middle ages in China, North Africa and Central America [6]. The major components isolated from the Amaryllidaceae plant family are alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in chemotherapy, radiotherapy and surgical interventions, the clinical outcome of GBMs is poor and a better understanding of glioma biology is needed in order to develop better therapeutic options. Recent studies have investigated the anti-oncogenic properties of natural products and several of these studies have shown that natural product extracts exhibit anti-oncogenic properties against various types of cancer [3][4][5][6][7]. Specifically, there has been a renewed effort to examine the anti-oncogenic properties of natural products for the treatment of GBM cells [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…treatment of diabetes, for ear and chest ailments and against viral infections. Traditional usage of this genus from very simple health problems like head ache, cough and cold, boils to very complicated diseases like breast cancer, tuberculosis, rheumatism, tumors shows its importance in treatment of various diseases [2,11,12].…”
Section: Traditional Usagementioning
confidence: 99%